Utilization of Telestroke during Pandemic COVID-19: A Scoping Review - Khairari, Nandang DD (Journal of Health Policy and Management, 2022)
Background: Telehealth in the setting of patient with stroke or widely known as a telestroke has been researched and practiced in various ways in past decades, but recently with the appearance of pandemic Covid-19 the utilization of telestroke needs to synthesis of the existing literature. This has been reported that there are changes in the utilization of of technology-based health services, includes in the use of telestroke. This study aims to review the utilization of telestroke during this recent pandemic Covid-19. Subjects and Method: This study used scoping review as a method to answer the research question. The study was permormed by searching PubMed, Science Direct, BMJ, and Wiley Online Library databases from 2020 to June 2022. The studies that investigating the uses of telestroke during the period of pandemic Covid-19 were included to this scoping review. The PEOS framework and PRISMA flowchart has been utilized as a method to identifying and selecting the studies, as well as inclusion and exclusion criteria. Results: There were 8 studies that relevant to inclusion criteria and reviewed in this study. The majority of telestroke studies were observational study using retrospective method. Five studies stated that the decreased number of utilization of telestroke during pandemic. Demographic characteristics of the study shown the mean age were >60 years old (87.5%), female patients were more than male (62.5%), primary diagnosed with ischemic stroke (87.5%), severity from mild to severe (62.5%), stroke patients were received thrombolysis (75%), and two studies stated shorter duration for patient to receive treatment.Conclusion: Telestroke has been proven as an effective way in caring patient with stroke. Significant decreased number of telestroke admission was shown from most of the studies due to the Covid-19 while the explanation for this phenomena is still unclear.Keywords: Telestroke, Covid-19, Scoping Review.Correspondence: Nandang DD Khairari. Bachelor in Nursing Program of Hamzar Institute of Health Science. Jalan TGH. Zainuddin Arsyad, No : 100, Wanasaba District, East Lombok Region, West Nusa Tenggara. Dhe2304@gmail.com. Mobile. 0877-6505-6560.Journal of Health Policy and Management (2022), 07(03): 235-242 https://doi.org/10.26911/thejhpm.2022.07.03.08